Study on the Effectiveness of Enhanced Recovery After Surgery (ERAS) Protocols in Gastrointestinal Surgery - Dr. Asif, Dr. Ramesh C Sagar, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Enhanced Recovery After Surgery (ERAS) protocols are organized, team-based care plans that aim to lowersurgical stress, improve body function, and help patients recover more quickly. Using these protocols in gastrointestinal (GI) surgery has shown better postoperative results compared to traditional care.